Blind Satellite Inter-Gateway Interference Mitigation - J. Arnau; C. Mosquera (IEEE International Conference on Communications (ICC), 2015)
Keywords: compass; satcom

Multibeam Joint Detection - J. Arnau; R. de Lamare; C. Mosquera (Cooperative and Cognitive Satellite Systems, 2015)
Keywords: satcom

Balancing Closed and Open Loop CSI in Mobile Satellite Link Adaptation - Alberto Rico-Alvariño; Arnau, Jesus; Carlos Mosquera (Proc. ASMS & SPSC, 2014)
Keywords: dynacs; satcom

Dissection of multibeam satellite communications with a large-scale antenna system toolbox - Arnau, Jesus; Carlos Mosquera (European Wireless 2014 (EW2014), 2014)
Current multibeam satellite systems consist of a very large number of spot beams. In this paper, we analyze them from the large scale MIMO perspective, and establish a comparison with massive MIMO systems. It will be shown that the large number of beams has important operational implications, and that it simplifies the analysis because it allows using asymptotic results. However, it will also be shown that multibeam satellite systems cannot be considered massive MIMO systems.
Keywords: dynacs; large-scale analysis; Massive MIMO; multibeam satellites; Multiuser detection; satcom

On-Ground Processing for Spectral Efficiency Improvement in Next Generation Satellite Communications - Arnau, Jesus (Universidade de Vigo, 2014)
The eternal demand of improved spectrum exploitation for next generation satellite communications requires the study of techniques that are potentially able of a breakthrough. In this thesis we focus on two of the main issues hindering the performance of satellite communications.   In the first part of the thesis, we study the use of multi-user detection techniques in the return link of multibeam satellite systems operated with an aggressive frequency reuse strategy. We start by comparing their performance with respect to a traditional scenario, and study the possibility of splitting the processing between the gateway and the satellite to cope with practical constraints. We then study the fundamental performance limits of such a system when spatially correlated rain attenuation affects the users; analytical expressions are obtained for the high and low SNR regimes. Finally, we consider non perfect channel state information and obtain, through random matrix theory, an approximation of the residual error as a function of the system's parameters.   In the second part, we focus on link adaptation for mobile satellite communications. For the return link, we investigate the potential of open-loop channel state information, which is timely but scarcely accurate; the finding that this information is better than the traditional closed-loop one depending on the channel conditions motivated the study of an adaptive algorithm to dynamically balance both. Finally, in the forward link we considered the case where retransmissions are available, and designed the optimum modulation and coding scheme sequence for the different retransmissions of a packet in terms of throughput.
Keywords: satcom

Performance of the Multibeam Satellite Return Link with Correlated Rain Attenuation - Arnau, Jesus; Christopoulos, D.; Chatzinotas, S.; C. Mosquera; Ottersten, B. (IEEE Transactions on Wireless Communications, 2014)
Rain attenuation is among the major impairments for satellite systems operating in the K band and above. In this paper, we investigate the impact of spatially correlated rain attenuation on the performance of a multibeam satellite return link. For a comprehensive assessment, an analytical model for the antenna pattern that generates the beams is also proposed. We focus on the outage capacity of the link, and obtain analytical approximations at high and low SNR. The derived approximations provide insights on the effect of key system parameters – like the inter-user distance, the satellite beam radius, or the rain intensity– and simulation results show that it fits tightly to the Monte Carlo results. Additionally, the derived expressions can be easily particularized for the single-user case, providing some novel insights.
Keywords: Antennas; Approximation methods; Attenuation; Correlation; dynacs; Rain; satcom; Satellites; Signal to noise ratio

Cross Layer Link Adaptation in Time Varying Mobile Satellite Channels with Statistical and Outdated CSIT - Alberto Rico-Alvariño; J. Arnau; Carlos Mosquera (Asilomar Conference on Signals Systems and Computers, 2013)
Keywords: dynacs; satcom

MMSE Performance Analysis of Generalized Multibeam Satellite Channels - Christopoulos, D.; J. Arnau; Chatzinotas, S.; C. Mosquera; Ottersten, B. (Communications Letters, IEEE, 2013)
Keywords: dynacs; linear minimum mean square error receivers; multibeam satellites; Multiuser detection; return link; satcom

Open Loop Adaptive Coding and Modulation for Mobile Satellite Return Links - Arnau, Jesus; Carlos Mosquera (31st AIAA International Communications Satellite Systems Conference, 2013)
Keywords: dynacs; link adaptation; satcom

Statistical Cross Layer Adaptation in Fast Fading Mobile Satellite Channels - Alberto Rico-Alvariño; J. Arnau; C. Mosquera (Globecom 2013 - Symposium on Selected Areas in Communications (GC13 SAC), 2013)
Link adaptation in mobile satellite channels is difficult because of the large propagation delays, the frequent signal blockage and the variation of the channel statistics. In this paper, we propose a cross-layer link adaptation strategy that exploits statistical, long-term CSI to increase the throughput when some retransmissions are available; this increase is obtained while meeting a target outage probability constraint. Our strategy takes as inputs the estimated packet error rates of the available modulation and coding schemes (MCS) and their rates; as an output, it returns the optimum sequence of MCS to be used. Results will also show that simple information acquisition strategies can still provide very good results.
Keywords: dynacs; fast fading channels; link adaptation; mobile satellite; satcom

Adaptive Transmission Techniques for Mobile Satellite Links - Arnau, Jesus; Alberto Rico-Alvariño; C. Mosquera (30th AIAA International Communications Satellite Systems Conference (ICSSC), 2012)
Keywords: dynacs; satcom

Multiuser Detection Performance in Multibeam Satellite Links under Imperfect CSI - Arnau, Jesus; C. Mosquera (ASILOMAR 2012, 2012)
Keywords: dynacs; satcom

Performance Analysis of Multiuser Detection for Multibeam Satellites Under Rain Fading - Arnau, Jesus; C. Mosquera (2012 6th Advanced Satellite Multimedia Systems Conference (ASMS) and 12th Signal Processing for Space Communications Workshop (SPSC) (ASMS/SPSC 2012), 2012)
Multibeam satellite systems are nowadays widely employed, and their use is expected to grow in the next decades. This has raised the interest for signal processing techniques able to mitigate the interference among beams, since they could enable a much more aggressive spectrum reuse. From an engineering point of view, the design of the system must be no longer based on the capabilities provided by the usual physical layer; it should take into account the presence of these interference canceling techniques, predict their performance as accurately as possible -even under a number of impairments and non-idealities- and design accordingly in order to fully exploit them. In this paper, we investigate the effect of a practical impairment of great importance, namely, the attenuation due to the rain, on the performance of a return link which performs MMSE interference canceling. Analytical expressions are derived for a number of performance measures based on the statistical characterization of the rain attenuation.
Keywords: dynacs; hybrid beamforming; multibeam satellites.; Multiuser detection; rain fading; satcom

Performance study of multiuser interference mitigation schemes for hybrid broadband multibeam satellite architectures - Arnau, Jesus; Bertrand Devillers; C. Mosquera; Ana Pérez-Neira (EURASIP Journal on Wireless Communications and Networking, 2012)

Hybrid Space-Ground Processing for High-Capacity Multi-beam Satellite Systems - Arnau, Jesus; Michael Bergmann; Enzo Alberto Candreva; Giovanni Emanuele Corazza; Riccardo De Gaudenzi; Bertrand Devillers; Wilfried Gappmair; Francesco Lombardo; C. Mosquera; Ana Pérez-Neira; Ilaria Thibault; Alessandro Vanelli-Coralli (IEEE GLOBECOM, 2011)
Selected Areas in Communications Symposium - Satellite & Space Communications Track (GC'11 - SAC - SSC)